PRODUCTIVITY OF EARLY MATURING SOYBEAN VARIETIES IN THE LEFT-BANK FOREST-STEPPE OF UKRAINE - Shovkova, O. (Scientific Progress & Innovations, 2022)
Soybean is an important high-protein and oilseed crop in Ukraine and worldwide. Almost half of the success of growing this crop depends on the right choice of variety and seeding date. Adjusting the seeding date makes it possible to influence the supply of soybean plants with heat and moisture in a changing climate. The aim of the research was to fix the optimal seeding terms of early maturing soybean varieties under the conditions of the left-bank forest-steppe of Ukraine. The task of the research was to determine the effect of seeding terms on the growth and development of plants as well as the formation of seed yield of early maturing soybean varieties. The following scientific methods were used in the research: analysis, synthesis, field and statistical methods. The research results proved that soybean plants of early maturing varieties responded differently to the shifting of seeding terms. The variety Cassidi turned out to be the most productive among early maturing soybean varieties. When sown in the second term, its seed yield increased by 0.11 t/ha or 4.2 % compared with the first term and by 0.26 t/ha or 9.8 % compared with the third seeding term. The productivity of the variety Amadeus on average for three years of research ranged from 2.26 t/ha in the third seeding term to 2.53 t/ha in the second seeding term. The variety Triada had the highest productivity in the second seeding term – 2.40 t/ha, which is 0.11 t/ha or 4.6 % more than in the first seeding term, by 0.23 t/ha or 9.6 % more than in the third seeding term. The best conditions for the productivity formation of the variety Sophia were also in the second term of sowing crop – 2.33 t/ha. An economic evaluation of cultivation technology indicates that for the sowing of early maturing soybean varieties in the second term, the net profit was the highest, which amounted to 16815–21455 UAH/ha, and the level of profitability of the crop was 99.09–126.43 %. Experimental research data showed that sowing of early maturing soybean varieties in the second term was the most effective (I decade of May).